2020
DOI: 10.3390/ijms21124348
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Attenuates Pancreatic and Renal D-Galactose-Induced Aging-Related Oxidative Alterations in Rats

Abstract: Aging is an oxidative stress-associated process that progresses with age. Our aim is to delay or attenuate these oxidative alterations and to keep individuals healthy as they age using natural compounds supplementation. Therefore, we conducted the present study to investigate the protective potentials of quercetin against D-galactose (D-gal)-associated oxidative alterations that were induced experimentally in male Wistar rats. Forty-five rats were randomly allocated into five groups of nine rats each. The grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 61 publications
4
45
0
Order By: Relevance
“…This may be explained by the ability of quercetin to reduce the ROS therefore inhibiting lipid peroxidation and preventing the formation of MDA [ 33 ]. This was attributed to the catechol group (B ring) and the OH group at position 3 of the A and C ring, which have optimal free-radical scavenging [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be explained by the ability of quercetin to reduce the ROS therefore inhibiting lipid peroxidation and preventing the formation of MDA [ 33 ]. This was attributed to the catechol group (B ring) and the OH group at position 3 of the A and C ring, which have optimal free-radical scavenging [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin (3, 3′, 4′, 5, 7-pentahydroxyflavone) is a flavonoid present in fruits (apples, berries, cherries and red grapes) and vegetables (onions and broccoli) in addition to many seeds, buckwheat, nuts, flowers, barks, green tea and olive oil [ 10 ]. Quercetin has plentiful valuable effects comprising anti-inflammatory, anti-oxidant, anti-mutagenic, anti-ischemic, anti-viral and anti-aging effects [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Quercetin is lipophilic and can penetrate the blood-brain barrier (BBB) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin has many biological functions including anti-oxidant, antiinflammatory, and immune-regulatory activities (17)(18)(19). Quercetin supplementation had been shown to attenuate D-Galactose-induced renal damage in rats and aflatoxin B1-induced neurotoxicity in mice through the inhibition of oxidative stress (20,21). A recent study also showed that quercetin supplementation could inhibit lipopolysaccharide (LPS)-induced inflammation in a proximal tubular cell line human kidney 2 (HK-2) cells which derived from normal human kidney (22).…”
Section: Introductionmentioning
confidence: 99%
“…Park et al had investigated quercetin against ischemic brain injury and demonstrated that ischemia-induced glutamate and caspase-3 increases were effectively suppressed [25]. Examining the effects of quercetin supplementation against aging caused by D-galactose in the pancreatic and kidney tissues, El-Far and colleagues reported that this substance may be effective in preventing aging-related oxidant damage and suppress apoptotic and inflammatory events [26]. Furthermore, in doxorubicin-induced cardiotoxicity, quercetin treatment, by increasing the antioxidant levels, suppressed ROS formation and caspase activity and thereby corrected the mitochondrial function [27].…”
Section: Discussionmentioning
confidence: 99%